Respuesta :

The expression (2x) . (x²+3) = 5 gives the solution and the solutions for the given equation are x = 2.5, x=√2 , x= -√ 2

Step-by-step explanation:

  • The given equation is that  [tex]-5 +2x^{3}=-6x[/tex].
  • From the equation given, it can be determined that it contains x terms and a constant term.

So, bring x terms alone on one side and keep the constant on the other side of the equation. When moving a term from one side of the equation to other side, the sign changes.

Now, the equation becomes [tex]2x^{3} + 6x = 5[/tex].

To find the solution by solving the x value :

Take the common term outside, that is 2x is common and it taken out as a common factor.

⇒ 2x (x²+3) = 5

⇒ (2x) . (x²+3) = 5

The above expression gives the solution.

Therefore, 2x = 5 and (x²+3) = 5

For 2x = 5,

⇒ x = 5/2

x = 2.5

For (x²+3) = 5,

⇒ x² = 5-3

⇒ x² = 2

Taking square root on both sides,

⇒ x = ± √2

x = √2 and x = -√2

ACCESS MORE